2024
DOI: 10.1681/asn.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Identifies Response of Renal Lymphatic Endothelial Cells to Acute Kidney Injury

Heidi A. Creed,
Saranya Kannan,
Brittany L. Tate
et al.

Abstract: Significance Statement The renal lymphatic vasculature and the lymphatic endothelial cells that make up this network play important immunomodulatory roles during inflammation. How lymphatics respond to AKI may affect AKI outcomes. The authors used single-cell RNA sequencing to characterize mouse renal lymphatic endothelial cells in quiescent and cisplatin-injured kidneys. lymphatic endothelial cell gene expression changes were confirmed in ischemia–reperfusion injury and in cultured lymphatic endot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The occurrence and development of renal ischemia-reperfusion injury (IRI) might mediate inflammatory response through inflammation-related signaling pathways, and blocking inflammatory response plays a very important role in improving the pathological status of AKI ( Li et al, 2022 ; Creed et al, 2024 ). Relevant studies ( Vande Walle and Lamkanfi, 2024 ; Xu K. et al, 2024 ) have shown that pyroptosis is a key mechanism of renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and development of renal ischemia-reperfusion injury (IRI) might mediate inflammatory response through inflammation-related signaling pathways, and blocking inflammatory response plays a very important role in improving the pathological status of AKI ( Li et al, 2022 ; Creed et al, 2024 ). Relevant studies ( Vande Walle and Lamkanfi, 2024 ; Xu K. et al, 2024 ) have shown that pyroptosis is a key mechanism of renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this issue of JASN, Creed et al provide additional insights into the implications of lymphatic biology for kidney diseases. 3 By exploring the altered gene expression changes in response to cisplatin-induced AKI in male mice, the investigators identified the lymphatic endothelial cells (LECs) molecular signature as being most consistent with vascular endothelial growth factor receptor signaling, T-cell differentiation, and regulation of inflammatory response, supporting the notion that LECs respond to AKI by undergoing lymphangiogenesis and upregulating their interactions with immune cells. In addition, by comparing the molecular responses of LECs to distinct injury stimuli (cisplatin versus ischemia-reperfusion injury), the investigators revealed that the response of LECs is likely influenced by the specific mode and context of injury, thereby substantiating the existing evidence of conflicting outcomes in the literature across different models.…”
mentioning
confidence: 91%